Contribution of lung migratory dendritic cells to the generation of influenza immunity - Ng, See Liang (2015)
Owing to the functional heterogeneity of DCs in the lung, there is a need to unravel the in vivo contribution of various DC subpopulations to the generation of influenza immunity. Using our Clec9a-DTR and Clec4a4-DTR transgenic mouse models which allow us to specifically deplete CD103+ cDCs and CD24+CD11b+ cDCs respectively in the lungs, we aimed to study the biology of these DC populations using mouse-adapted influenza A virus strain H1N1/PR8. We found that ablation of these lung-derived DCs led to high sensitivity to infection and severe depletion of influenza-virus specific CD8 T cells in the lungs and more importantly the mechanisms contributing to the reduced number of these pulmonary T cells in Clec9a-DTR and Clec4a4-DTR mice were different. Concurrently our data highlighted the dispensability of these DCs in the formation of homosubtypic immunity, but, they were required for the efficacy of heterosubtypic immunity.